2018
DOI: 10.1002/cam4.1904
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of radiotherapy for early‐stage hormone receptor‐positive breast cancer in elderly women using real‐world data

Abstract: BackgroundRadiotherapy is the recommended treatment after breast‐conserving surgery (BCS) for early‐stage breast cancer (BC). However, there is no clear evidence whether radiotherapy after BCS improves the survival of elderly women diagnosed with early‐stage hormone receptor‐positive (HR+) BC. The aim of this study was to investigate the survival benefit associated with radiotherapy plus hormonal therapy vs hormonal therapy alone after BCS for early‐stage HR+ BC patients.MethodsUsing the Surveillance, Epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Moreover, some observational studies and a large propensity-score study showed a decreased risk of death for elderly breast cancer patients treated with RT ( 10 - 12 ). Ali et al analysed a total of 5,688 patients, 1,549 (27.23%) of whom treated with hormone therapy (HT) alone and 4,139 (72.77%) treated with RT plus HT after BCS ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some observational studies and a large propensity-score study showed a decreased risk of death for elderly breast cancer patients treated with RT ( 10 - 12 ). Ali et al analysed a total of 5,688 patients, 1,549 (27.23%) of whom treated with hormone therapy (HT) alone and 4,139 (72.77%) treated with RT plus HT after BCS ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some observational studies and a large propensity-score study showed a decreased risk of death for elderly breast cancer patients treated with RT ( 10 - 12 ). Ali et al analysed a total of 5,688 patients, 1,549 (27.23%) of whom treated with hormone therapy (HT) alone and 4,139 (72.77%) treated with RT plus HT after BCS ( 12 ). In the Propensity Score-matched sample, patients who had received RT plus HT revealed a 38% lower risk of death compared with patients who were treated with only HT ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous observational studies addressed the omission of radiotherapy after BCS in older patients. Some advocate that radiotherapy may be omitted [20][21][22][23], whereas others state that it is unsafe due to a higher risk of locoregional recurrence [24][25][26] or even worse breast cancer specific and overall survival [25,[27][28][29]. Although different patient selections could play a role in the varying findings, results of these studies using conventional methods to adjust for confounding may have been biased to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, the U.S. national guidelines recommended omitting adjuvant radiotherapy after BCS for EBC women 70 years of age and older who are prescribed endocrine therapy [ 9 ]. However, whether radiotherapy is beneficial in the elderly is still a matter of debate, with results of recent studies using observational real-world data reporting higher mortality rates in those who did not receive radiotherapy after BCS [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%